The Impact of Raising Phonological Awareness and Phonics to Improve Reading and Spelling Skills - Alharthy, Najla (My University, 2019)
This research identifies the impact of raising phonological awareness and phonics to improve reading and spelling skills among elementary age students in Saudi Arabia during English as a second language instruction. This initiative will occur over three years. It will begin in the AL Baha district and eventually reach all Saudi Arabia school districts. As one of the Khbrat program scholars, at Kansas State University in United States of America, I have had the chance to observe various techniques and approaches using phonemic awareness and phonics in English language arts instruction that can be shared with educators to ensure the success of the students in this project. Moreover, teachers will gain a renewed interest in teaching reading and hopefully there will be an overall increase in positive attitudes regarding reading instruction.
Keywords: Effectiveness of phonics and phonological awareness on ESL learner